The Halal Industry in Asia (Springer Nature, 2025)
This innovative, open access volume explores the core characteristics of the halal industry through case studies of five East and Southeast Asian countries—Brunei Darussalam, Malaysia, Japan, Indonesia and China—representing both Muslim-majority and Muslim-minority societies. The contributors focus on some of the leading sectors of the Islamic economy, comprising food, finance, pharmaceuticals, and travel and tourism, in order to diagnose the challenges they face and the opportunities that present themselves. Particular attention is given to issues of certification and compliance, quality assurance, human resource development, education, legal frameworks, logistics and supply chains, innovation, sustainability, and growth potential beyond the core Muslim consumers in order to offer a critical assessment of the state of the halal industry in comparative perspective. The book shows that one of the most remarkable features of the world economy over the last two decades has been the emergence and sustained growth of the global halal industry. This has been underpinned by several key factors, including a young and expanding Muslim population, Islamic faith-inspired consumption, and a number of public and private strategies dedicated to halal product and service development. This is a significant achievement, especially given major disruptions and risks such as geopolitical instability, the worsening climate crisis, the impact of the Covid-19 pandemic and the uncertainties associated with AI and automation. Academic scholars, university students and others interested in the study of the current state of the halal industry in Asia and broader questions of the global Islamic economy will find this volume an invaluable resource to enable them to understand these pressing challenges and navigate this opportunity landscape. ; This innovative, open access volume explores the core characteristics of the halal industry through case studies of five East and Southeast Asian countries—Brunei Darussalam, Malaysia, Japan, Indonesia and China—representing both Muslim-majority and Muslim-minority societies. The contributors focus on some of the leading sectors of the Islamic economy, comprising food, finance, pharmaceuticals, and travel and tourism, in order to diagnose the challenges they face and the opportunities that present themselves. Particular attention is given to issues of certification and compliance, quality assurance, human resource development, education, legal frameworks, logistics and supply chains, innovation, sustainability, and growth potential beyond the core Muslim consumers in order to offer a critical assessment of the state of the halal industry in comparative perspective. The book shows that one of the most remarkable features of the world economy over the last two decades has been the emergence and sustained growth of the global halal industry. This has been underpinned by several key factors, including a young and expanding Muslim population, Islamic faith-inspired consumption, and a number of public and private strategies dedicated to halal product and service development. This is a significant achievement, especially given major disruptions and risks such as geopolitical instability, the worsening climate crisis, the impact of the Covid-19 pandemic and the uncertainties associated with AI and automation. Academic scholars, university students and others interested in the study of the current state of the halal industry in Asia and broader questions of the global Islamic economy will find this volume an invaluable resource to enable them to understand these pressing challenges and navigate this opportunity landscape.